Corticocortical paired associative stimulation for treating motor dysfunction after stroke: study protocol for a randomised sham-controlled double-blind clinical trial. Issue 1 (13th January 2022) - Duan, Yu-Jie; Hua, Xu-Yun; Zheng, Mou-Xiong; Wu, Jia-Jia; Xing, Xiang-Xin; Li, Yu-Lin; Xu, Jian-Guang
Abstract : Introduction: Stroke survivors can have a high disability rate with low quality of daily life, resulting in a heavy burden on family and society. Transcranial magnetic stimulation has been widely applied to brain injury repair, neurological disease treatment, cognition and emotion regulation and so on. However, there is still much to be desired in the theories of using these neuromodulation techniques to treat stroke-caused hemiplegia. It is generally recognised that synaptic plasticity is an important basis for functional repair after brain injury. This study protocol aims to examine the corticocortical paired associative stimulation (ccPAS) for inducing synaptic plasticity to rescue the paralysed after stroke. Methods and analysis: The current study is designed as a 14-week double-blind randomised sham-controlled clinical trial, composed of 2-week intervention and 12-week follow-up. For the study, 42 patients who had a stroke aged 40–70 will be recruited, who are randomly assigned either to the ccPAS intervention group, or to the control group at a 1:1 ratio, hence an equal number each. In the intervention group, ccPAS is practised in conjunction with the conventional rehabilitation treatment, and in the control group, the conventional rehabilitation treatment is administered with sham stimulation. A total of 10 interventions will be made, 5 times a week for 2 weeks. The same assessors are supposed to evaluate the participants' motor function at four time points of the baseline (before 10 interventions), treatment ending (after 10 interventions), and two intervals of follow-up (1 and 3 months later, respectively). The Fugl-Meyer Assessment Upper Extremity is used for the primary outcomes. The secondary outcomes include changes in the assessment of Action Research Arm Test (ARAT), Modified Barthel Index (MBI), electroencephalogram (EEG) and functional MRI data. The adverse events are to be recorded throughout the study. Ethics and dissemination: This study was approved by the Medical Ethics Committee of Yueyang Hospital. All ethical work was performed in accordance with the Helsinki declaration. Written informed consent was obtained from all individual participants included in the study. Study findings will be disseminated in the printed media. Trial registration number: Chinese Clinical Trial Registry: ChiCTR2000036685.